2017
DOI: 10.5812/ijp.8211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nebulized Albuterol in Transient Tachypnea of the Newborn A Clinical Trial

Abstract: Background: To date there is no effective drug treatment for transient tachypnea of the newborn (TTN) and respiratory support is the only means to handle this disease. This study was performed to evaluate the effect of albuterol (Salbutamol) in improvement of respiratory distress in involved neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Regarding the adverse effects of epinephrine and salbutamol inhalations such as tachycardia, hypokalemia, and hypoglycemia, there were no statistically signi cant differences between all the studied groups Table (3). Similarly, all the previous trials using either epinephrine or salbutamol inhalation did not demonstrate any adverse effects from those interventions for both single and multiple doses 2,10,19,20,21,23,25,26,27,28 . It depicts the safety and tolerability of these interventions as reported by the current study and the previous studies.…”
Section: Adverse Effectsmentioning
confidence: 73%
“…Regarding the adverse effects of epinephrine and salbutamol inhalations such as tachycardia, hypokalemia, and hypoglycemia, there were no statistically signi cant differences between all the studied groups Table (3). Similarly, all the previous trials using either epinephrine or salbutamol inhalation did not demonstrate any adverse effects from those interventions for both single and multiple doses 2,10,19,20,21,23,25,26,27,28 . It depicts the safety and tolerability of these interventions as reported by the current study and the previous studies.…”
Section: Adverse Effectsmentioning
confidence: 73%
“…The need for positive pressure ventilation was decreased in those babies who were given Salbutamol inhalation. 17 Similarly, another study conducted by Armangil et al, on the possible effects of Salbutmol inhalation on 54 infants with TTN revealed reduced need for oxygen support and mechanical ventilation after the initial 30 minutes of Salbutamol inhalation. 20 A Korean study evaluated the effects of inhaled Salbutamol in TTN demonstrated reduction of tachypnea in the infants receiving Salbutamol intervention and also the duration of supplemental oxygen requirement.…”
Section: Discussionmentioning
confidence: 86%
“…13,14,15 The incidence of TTN in Pakistan was found to be 14.1%. 16,17 At birth, the release of catecholamines, steroids and vasopressin affect the balance of fluid in the alveoli from fluid secretion to fluid absorption, thereby facilitating the adaptation to ex-utero enviornment. 18,19 NICUs in developing countries like Pakistan have limited resources and are overburdened with neonates diagnosed with TTN.…”
Section: Discussionmentioning
confidence: 99%
“…16 On the other hand, Mussavi et al While conducting a study on TTN, identified equal gender distribution (male 51.7%) with an average birth weight of 2.70kg and mean gestational age of 36.9 weeks. 17 On the contrary, Kaur et al in India found a male predominance as 65% of their studied newborns were male. 18 In our patients, TTN scores before and 4 hours after treatment with Salbutamol were 8.30±1.37 and 2.67±0.76, respectively, with an observed mean change of 5.63±1.22.…”
Section: Discussionmentioning
confidence: 88%
“…In a randomized controlled trial conducted in Iran, Mussavi et al also managed 60 neonates with TTN on CPAP and improvement was witnessed with albuterol nebulization (0.15 mg/kg) as respiratory distress score improved from 5.6 to 1.7, in contrast to 5.6 to 3.9 in the placebo group (saline nebulization). 17 However, in India, Basiri et al while managing 100 newborns with TTN on nasal prong oxygen at the gestational age of 35-41 weeks, failed to identify any improvement in TTN Score before and 4 hours after Salbutamol (0.15 mg/kg) nebulization as the reported scores were 5.7 and 5.4 respectively. 18 In our study group, RR (respiratory rate) was 69.43±4.25 per minute before Salbutamol administration, with the exhibited change of 9.80±2.05 post salbutamol.…”
Section: Discussionmentioning
confidence: 99%